Evaluación de factores de riesgo ergonómicos en el área de producción y su incidencia en la salud de los trabajadores de la empresa " INJOBER " en la ciudad de Latacunga. - Cajilema Fernández, Lorena Beatriz (2018)
The identification and evaluation of ergonomic risk factors for each activity carried out in the workplace is the most important part of the occupational health and safety area since it takes care of the integrity of the employees of the company "INJOBER". The interpretation of the level of risk that determines the state in which the production area was developed was carried out by using the Reba method that allowed assessing the risks according to: the relationship between exposure to certain positions, the force used and the type of muscular activity used with respect to the risk of the activity, this evaluation was performed in the jobs that correspond to the production process. The needs of the industry with respect to the production process were observed and corrective measures were recommended such as: elimination of ergonomic risks. The project is of great importance in the part of the person since to verify and know the risks will allow employees to mitigate ergonomic risks so that there is a preventive activity to take care of their health, in the economic part it will help the company to avoid professional illnesses and mitigate incident and accidents that employees may suffer if the measures belonging to them are not taken.